The Potential of Riparian Ecosystems for Ecotourism Development in The Ilomata Village Forest Area, Bone Bolango Regency, Gorontalo, Indonesia - Diva M.A. Saghita Putri; Marini Susanti Hamidun; Dewi Wahyuni K. Baderan (Indonesian Journal of Chemistry and Environment, 2025)
This study aimed to analyze the potential and feasibility of ecotourism development within the riparian ecosystem of the Ilomata Village Forest Area, Bone Bolango Regency. A quantitative descriptive method was applied. Data on vegetation and fauna were collected through an exploratory survey conducted along the riparian zone of the Ilomata tourism site. Ecotourism feasibility was assessed using the Evaluation Instrument for Natural Tourism Objects and Attractions (ODO-ODTWA). The results showed that the riparian area hosts 13 plant species, dominated by Piper aduncum, Arenga pinnata Merr., and Ficus septica among the higher plant category, while the lower vegetation layer was dominated by ferns such as Phymatosorus scolopendria, Chromolaena odorata, and Dryopteris filix-mas (L.) Schoot. The fauna identified was predominantly from the Class Insecta, including the butterfly Vindula dejone as the most frequently observed species. The ecotourism feasibility index for the Ilomata riparian ecosystem was recorded at 59.3%, indicating a moderately feasible category. The attraction, environment and community, and management and services components received relatively high scores, whereas accessibility and tourism facilities were rated low. Therefore, improving accessibility and tourism infrastructure is necessary to support the development of sustainable ecotourism in the area.